2016
DOI: 10.1002/pc.24090
|View full text |Cite
|
Sign up to set email alerts
|

The effects of MgO nanofiller to the physicochemical and ionic liquid retention properties of PEMA‐MgTf2‐EMITFSI nanocomposite polymer electrolytes

Abstract: Nanocomposite polymer electrolytes were prepared by dispersing different compositions of nanosized magnesium oxide (MgO) as ceramic nanofiller in poly(ethyl methacrylate) (PEMA)220 wt% magnesium triflate (MgTf 2 )240 wt% 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (EMITFSI) electrolytes. The role of ionic liquid, magnesium salt, and ceramic nanofiller were visualized by various physical and electrochemical analyses including scanning electron microscopy, thermogravimetric analysis, electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…25,34 The dispersal of nanofillers into the optimized GPEs works as an insulating surface thus averting the heat from expanding swiftly and increases the thermal stability of NCGPE sample noticeably to approximately 185°C. 35…”
Section: Resultsmentioning
confidence: 99%
“…25,34 The dispersal of nanofillers into the optimized GPEs works as an insulating surface thus averting the heat from expanding swiftly and increases the thermal stability of NCGPE sample noticeably to approximately 185°C. 35…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical stability was promoted a results of the addition of MgO NPs. The appearance of Mg deposition/desolution peak in CV curve showed that magnesium effectively migrating through electrolytes (i.e., the cathodic deposition and anodic oxidation of Mg are facile at the Mg/polymer electrolyte interface and therefore are indicative of Mg 2+ ion conduction in the polymer electrolyte .…”
Section: Resultsmentioning
confidence: 99%
“…Nho et al found that the highest ionic conductivity is 1.3 × 10 −3 S/cm of γ‐Al 2 O 3 /PVDF‐HFP/TTT (95/5/2) coated PE separator for lithium secondary battery. The improvement of electrical conductivity up to 3.78 × 10 −4 S/cm at 100°C of PEMA‐20 wt% MgTf 2 ‐40 wt% EMITFSI‐1 wt% of MgO nanofiller was obtained by Zain et al .…”
Section: Introductionmentioning
confidence: 89%